Hemolytic anemia in falciparum and vivax malarial patients based on serum bilirubin examination - Yoyoh Yusroh; Bidasari Lubis; Syahril Pasaribu; Munar Lubis; Tiangsa Sembiring; Adillida Adillida (Indonesian Pediatric Society, 2004)
Objective To examine hemolysis in falciparum and vivax malarialpatients based on serum bilirubin examination.Methods A cross sectional study was conducted on childrenyounger than 15 years of age who visited public health center inthe district of Mandailing Natal with complaints of fever, shivering,pale, jaundice, diarrhea, or headache between April 9 th and April19 th 2001. Variables recorded were age, gender, body weight, bodyheight, symptoms and signs, anti malarial drugs, and laboratorytest results. Thin and thick blood smears were done as diagnostictools of malaria. Thin blood smear was also performed to deter-mine the level of malaria parasites in blood (parasitemia) and toexamine the morphology of red blood cells. Hemolysis was deter-mined by bilirubin examination.Results In P. falciparum malaria, there was a moderate correlation(r=0.68, p<0.0001) between parasitemia and indirect bilirubin con-centration. While in P. vivax malaria, there was only a weak corre-lation (r=0.46, p=0.007) between parasitemia and indirect bilirubinconcentration. It was also found that in falciparum malaria, para-sitemia, total and indirect bilirubin concentrations were significantlyhigher than that in vivax malaria, with p values of 0.009, 0.015 and0.003, respectively.Conclusion Hemolysis in falciparum malaria is more severe thanthat in P. vivax malaria, with marked elevation of indirect bilirubin.The elevation of serum bilirubin correlated with parasitemia